Pengaruh Kinerja Keuangan dan Opini Audit terhadap Audit Report Lag pada Perusahaan Perbankan 2014 – 2017 - Fitri Ani; Yuli Chomsatu; Riana R Dewi (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
The purpose of this research is to test the influence of profitability, solvency, liquidity, corporate size and opinion of audits on the audit report lag of the company. Researchers use 31 companies listed on the Indonesia Stock Exchange period 2014 – 2017 from the audited company. Based on the results of hypothesis 1 testing which states profitability is approved for auditareports, the company's lag is supported by empirical evidence. Hypothesis testing 2, which was approved as solvency, was approved against the company's audit lag report which was not supported by empirical evidence. The hypothesis 3 test that states liquidity is recognized for the audit lag report is not supported by empirical evidence. Testing the fourth hypothesis stating company size was approved for audit lag reports is not supported by empirical evidence. Whereas the 5th hypothesis stating that audit opinion was approved for the audit lag report was not supported by the police.